Economic Transformation of UMKM in East Lombok Regency Through Digital Technology Innovation - Muliani; Defel Septian; Nukman (Universitas Pamulang, 2025)
This study aiming for explore utilization innovation digital technology against transformation economy Micro, Small, and Medium Enterprises (MSMEs) sector in East Lombok Regency. As entity economy strategic, UMKM in this region Still face fundamental challenges, such as limitations access technology, low digital literacy, as well as Not yet optimal ecosystem supporters. Gap literature identified in the minimum study empirical which focuses on the application of digital technology in context area rural with complexity socio-economic characteristics. This study use approach qualitative explorative with method interview deep to MSME actors and stakeholder local interest. Research results show that digitalization through utilization of e-commerce platforms, social media, and systems digital payments play a role significant in increase business process efficiency, expanding market reach, as well as push growth income. Although thus, its implementation Still faced with limitations infrastructure and inequality digital capabilities between perpetrator business. Novelty from study This lies in the approach contextual to digitalization of MSMEs in the regions rural as well as strategic model formulation based on potential local that can replicate in areas with characteristics similar. Implications from findings This expected can become runway for formulation policy empowerment an inclusive and sustainable digital economy.